Incidence and Clinical Outcome of Acute Liver Failure Caused by Dengue in a Hospital for Tropical Diseases, Thailand - Kye Mon, Khin (Am J Trop Med Hyg, 2016)
Acute liver failure is an atypical manifestation of dengue with a high mortality. We performed a retrospective cohort study at the Hospital for Tropical Diseases, Bangkok, Thailand. In total, 1,926 patients with serologically confirmed dengue were enrolled in the study from 2011 to 2015. Of these, six patients presented with acute liver failure, four died, and two survived. The incidence of dengue-associated acute liver failure was 0.31%. Dengue-associated acute liver failure was most common among young adults (median age, 29 years). The median duration from onset of fever to development of acute liver failure was 7.5 days. Patients with the severe stage of dengue had a higher risk of developing acute liver failure (P < 0.001). The baseline risk factors associated with the development of acute liver failure were an age of ≤ 40 years (odds ratio [OR] = 1.5, 95% confidence interval [CI] = 1.1–2.0, P < 0.05), a > 10% ratio of atypical lymphocytes (OR = 2.3, 95% CI = 1.8–3.0, P < 0.001), and a platelet count of < 50,000 mm(3) (OR = 2.8, 95% CI = 2.2–3.6, P < 0.001). The incidence of acute liver failure in patients with dengue was quite low, but its impact on morbidity, mortality, and poor clinical outcomes was significant. In summary, this study indicates that various baseline risk factors are associated with acute liver failure in patients with dengue.